Role of reactive oxygen species and mitochondrial damage in rheumatoid arthritis and targeted drugs - Jing, Weiyao; Liu, Cui; Su, Chenghong; Liu, Limei; Chen, Ping; Li, Xiangjun; Zhang, Xinghua; Yuan, Bo; Wang, Haidong; Du, Xiaozheng (Frontiers in Immunology, 2023)
Rheumatoid arthritis (RA) is an autoimmune disease characterized by synovial inflammation, pannus, and cartilage destruction and has a high disability rate. The hypoxic microenvironment of RA joints can cause reactive oxygen species (ROS) accumulation and mitochondrial damage, which not only affect the metabolic processes of immune cells and pathological changes in fibroblastic synovial cells but also upregulate the expression of several inflammatory pathways, ultimately promoting inflammation. In addition, ROS and mitochondrial damage are involved in angiogenesis and cartilage destruction, thereby accelerating RA progression. In this review, we highlight the effects of ROS accumulation and mitochondrial damage on the inflammatory response, angiogenesis, and cartilage destruction in RA. We also summarize therapies that target ROS or mitochondria to relieve RA symptoms and discuss the gaps in the studies and the controversies that exist, hoping to provide new ideas for research in this area and insights for targeted drug development in RA.